Safety and Biodistribution of an Autologous Bone Marrow-Derived Mononuclear Cell Infusion into Renal Arteries in Patients with Focal Segmental Glomerulosclerosis: A Phase 1 Study - Bruno Freire Botelho; André Luis Barreira; Marcio Gomes Filippo; Karina Dutra Asensi; Lanuza A P Faccioli; Anna Beatriz dos Santos Salgado; Elizabeth Figueiredo de Salles; Carlos Eduardo Cruz Marques; Pedro Leme Silva; Regina Coeli dos Santos Goldenberg; Angelo Maiolino; Bianca Gutfilen; et al. (Hindawi Limited, 2024)
Patients with focal segmental glomerulosclerosis (FSGS) who are refractory to drug treatment may present progressive loss of kidney function, leading to chronic kidney disease stage 5 under dialysis treatment. The safety of systemic administration of bone marrow-derived mononuclear cells (BMDMCs) has been shown in different preclinical models of kidney diseases. However, to date, no study has evaluated the safety and biodistribution of BMDMCs after infusion in renal arteries in patients with FSGS. We used a prospective, non-randomized, single-center longitudinal design to investigate this approach. Five patients with refractory FSGS and an estimated glomerular filtration rate (eGFR) between 20 and 40 ml/min/1.73 m2 underwent bone marrow aspiration and received an arterial infusion of autologous BMDMCs (5 × 107) for each kidney. In addition, BMDMCs labeled with technetium-99m (99mTc-BMDMCs) were used to assess the biodistribution by scintigraphy. All patients completed the 270-day follow-up protocol with no serious adverse events. A transient increase in creatinine was observed after the cell therapy, with improvement on day 30. 99mTc-BMDMCs were detected in both kidneys and counts were higher after 2 hr compared with 24 hr. The arterial infusion of BMDMCs in both kidneys of patients with FSGS was considered safe with stable eGFR at the end of follow-up. This trial is registered with NCT02693366.